Dendrobium fuscifaucium (Orchidaceae: Epidendroideae: Dendrobieae), a new Laotian species only known in cultivation - Souvannakhoummane, Keooudone; Kumar, Pankaj; Phonepaseuth, Phongphayboun (Phytotaxa, 2022)
Dendrobium fuscifaucium is described here as a new species from Laos PDR. This species was found at a local nursery and was claimed to have been collected from the limestone mountains of Kasi District (Vientiane Province). Detailed description and comparison, comparison with its allied species, D. hekouense, D. luoi and D. wangliangii is provided, along with flowering phenology and information on habitat. Multiple attempts have failed to locate this species in the wild.